Validation of the University Student Engagement Questionnaire in the Field of Education - Sara Cebrián Cifuentes; Empar Guerrero Valverde (MDPI AG, 2024)
In this study, the Student Engagement Questionnaire (SEQ) developed by Kember and Leung (2009), was validated using a Spanish sample. This instrument is intended to provide a comprehensive evaluation of teaching and learning processes within university contexts, offering feedback to educators and institutions to support the improvement of these processes. To achieve this, the SEQ was administered to a sample of 561 university students in the field of education, drawn from two universities in Valencia: the Universidad de Valencia (32%), a public institution, and the Universidad Católica de Valencia (68%), a private one, during the start of the first quarter. The questionnaire is designed to assess both students' competencies and teachers' abilities to foster a conducive learning environment. Across its various versions, the SEQ has demonstrated considerable stability in its dimensions and the relationships between the variables it assesses. Confirmatory factor analysis has validated the proposed structure in the Spanish population. As a result, the SEQ serves as a suitable instrument for diagnosing and evaluating the development of university students' competencies, as well as teachers' capacity to structure teaching and assessment in a way that promotes a constructive and enriching learning environment. Furthermore, it assists in identifying areas for improvement in the methodological strategies employed, enabling educators to refine their pedagogical approaches to maximise the impact on student learning and development.